PEMBAGIAN HARTA BERSAMA PASCA PERCERAIAN BAGI ISTERI YANG BERKARIER (STUDI TERHADAP PUTUSAN PENGADILAN AGAMA BENGKULU) - Nurul Hak; Meli Musli Marni (Qiyas : Jurnal Hukum Islam dan Peradilan, 2017)
Division of joint post-divorce property  for a career wife (a study of the Bengkulu  Religious Court’s decision). There  are two problems in this research, namely,  how  the concept of sharing  of joint property  for the wife of a career in the event  of divorce,  and what  is the basis of judges  consideration of Bengkulu  Religious Court in deciding the case of sharing  of joint property  for the  wife  of a career. Descriptive  qualitative  research method, while  data  collection techniques are  documentation,  observation and  interview.  Data  sources include  primary  and  secondary data.  The informant of the  judges  of the  Bengkulu  Religious Court. Secondary data  of religious  court  ruling on the  distribution of common property.  The results  of this study explain  that the distribution of joint property  for wives whose career is not clearly regulated in the  Compilation  of Islamic  Law, therefore in the  case  of sharing  of joint property  for the  wife of a career, becomes the ijtihad area  of the judge  to see  the case  casuistically  by taking into account the contribution and role of each.  Respectively.  The basis of consideration of the judges  of the Bengkulu Religious Court in determining the distribution of joint property  for wives of post-divorce careers, has been in accordance with theories based on the judges’ good judgment, procedurally in accordance with applicable law, because in its judgment the judge  has taken legal norms  Appropriate  to the articles  in the legislation,  and  has  fulfilled the normative juridical aspects, sociological and philosophical, so that the realization  of legal certainty,  legal justice and legal benefits.  Consideration of the judges of the Bengkulu  Religious Court in deciding the case  of sharing  of joint property  for the wife of the career, the majority of the decision based on the provisions  of the Compilation  of Islamic Law, some judges to explore  other sources of law as required Article 5 paragraph (1) Law Number  48 Year 2009 on Judicial Power  And the principle  of ius novita novit, in deciding the matter of sharing  the property  with the judges  of the Bengkulu  Religious Court based on casuistry.